Frontiers and hotspots of high-intensity interval exercise in children and adolescents: text mining and knowledge domain visualization - Sun, Fucheng (Frontiers in Physiology, 2024)
Background: During the past two decades, research on high-intensity interval exercise (HIIE) in children and adolescents has steadily accumulated, especially on the subthemes of improving cardiometabolic and cardiovascular health. However, there is still little scientific understanding of using scientometrics analysis to establish knowledge maps. Exploring the relationship between known and new emerging ideas, and their potential value, has theoretical and practical implications in context of a researcher's limited ability to read, analyze, and synthesize all published works. Objective: Firstly, to provide extensive information on HIIE research in children and adolescents, including authors, institutions, countries, journals, and references. Secondly, through co-occurrence, burst, and co-citation analyses based on hybrid node types, to reveal hotspots and to forecast frontiers for HIIE research in children and adolescents. Methods: Using the bibliographic data of the Web of Science Core Collection (WoSCC) as the data source, with the help of bibliometric methods and visualization tools CiteSpace, VOSviewer, Pajek, and Bibliometrix R-Package, publications, authors, and journals were analyzed. Authorial, institutional and national collaboration networks, as well as research hotspots and research frontiers based on keyword burst and document co-citations were plotted.Results: This study found that executive function, high-intensity interval training, heart rate variability, and insulin resistance are emerging research topics; high-intensity training, mental health, exercise intensity, and cardiometabolic risk factors are continual frontier research areas in the subthemes. Conclusion: Our study has three novel contributions. Firstly, it explicitly and directly reflects the research history and current situation of HIIE intervention strategy in children and adolescents. This approach makes it clear and easy to trace the origin and development of this strategy in specific groups of children and adolescents. Secondly, it analyzes the research hotspots of HIIE in the field and predicts the research frontiers and development trends, which will help researchers to have a deeper understanding of HIIE and pediatric health research. Thirdly, the findings will enable researchers to pinpoint the most influential scholars, institutions, journals, and references in the field, increasing the possibility of future collaborations between authors, institutions, and countries.